ANALISIS PERMINTAAN WISATAWAN MANCANEGARA BERWISATA DI TUKTUK SIADONG, KABUPATEN SAMOSIR - Atin Baoa Rorizki Hutasoit; Raina Linda Sari (Ekonomi dan Keuangan, 2014)
This thesis analyzes determinants of length of stay of international tourists on vacation in Tuktuk Siadong, Samosir regency, which is a major international tourism destination in Indonesia. Empirical modeling done by Ordinary Least Squares (OLS) and use primary data through questionnaires of 100 samples of international tourists in April 2014. Rising costs on vacation, quality of accommodation and infrastructure encouraging significantly increasing length of stay of tourists on vacation. Rising cost of vacation in other destination is complementary for adventurous international tourists in Indonesia, although not significantly reduce length for stay in Tuktuk Siadong. Income levels do not significantly increase demand for international tourists, but the beauty and serenity of nature gave pleasure to international tourists on vacation in Tuktuk Siadong.Key Words : International Tourist, Demand for Tourism, Tourism Costs, Income, Accommodation, Infrastructure